2013
DOI: 10.1073/pnas.1220143110
|View full text |Cite
|
Sign up to set email alerts
|

Differential hERG ion channel activity of ultrasmall gold nanoparticles

Abstract: Understanding the mechanism of toxicity of nanomaterials remains a challenge with respect to both mechanisms involved and product regulation. Here we show toxicity of ultrasmall gold nanoparticles (AuNPs). Depending on the ligand chemistry, 1.4-nm-diameter AuNPs failed electrophysiology-based safety testing using human embryonic kidney cell line 293 cells expressing human ether-á-go-go-Related gene ( hERG ), a Food and Drug Administration-established drug safety test. In patch-clamp exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 36 publications
(36 reference statements)
2
53
0
Order By: Relevance
“…For instance, only changing the strength of ligand affinity to the nanoparticle, without changing its size or charge, significantly affects the toxicity even for gold nanoparticles. This difference in soft and hard ligand corona effect has been recently reported and confirmed by molecular modelling to be caused by the blocking of ion channels by gold nanoparticles in embryonic kidney cells, with a stronger bio-response for the nanoparticles with the weaker bound ligands [39]. In organisms as sensitive as developing embryos even minute amounts of toxic material may have an impact and therefore cannot be excluded as a reason for the differences between the studies.…”
Section: Discussionmentioning
confidence: 75%
“…For instance, only changing the strength of ligand affinity to the nanoparticle, without changing its size or charge, significantly affects the toxicity even for gold nanoparticles. This difference in soft and hard ligand corona effect has been recently reported and confirmed by molecular modelling to be caused by the blocking of ion channels by gold nanoparticles in embryonic kidney cells, with a stronger bio-response for the nanoparticles with the weaker bound ligands [39]. In organisms as sensitive as developing embryos even minute amounts of toxic material may have an impact and therefore cannot be excluded as a reason for the differences between the studies.…”
Section: Discussionmentioning
confidence: 75%
“…The first and foremost consideration in selecting surface coating materials is that they should be biocompatible and non-toxic. For example, phosphine-stabilized AuNPs having size of 1.4 nm have been prepared but failed electrophysiologybased safety testing in human embryonic kidney cells, a safety test prescribed in FDA guideline (56). In addition, leaching of such surface coating materials may be problematic such as toxicity caused by cetyltrimethyl ammonium bromide CTAB, a famous stabilizing agent for AuNPs (57).…”
Section: Surface Chemistrymentioning
confidence: 99%
“…In a more recent study, ultrasmall gold nanoparticles were shown to irreversibly block hERG channels in patchclamp recordings (21). hERG forms the alpha subunit of one of the ion channel proteins that conducts potassium (K + ) ions in the heart.…”
Section: Towards a Molecular Nanotoxicologymentioning
confidence: 99%